Analisis Sosioteknologi: Pengembangan Inovasi Platform Wisata Religi Nusantara dengan Penerapan Prinsip Design Thinking dan Strategi Penetrasi Pasar - Yusrina Nuranisa Rahmatika; Octaviyanti Dwi Wahyurini (Fakultas Seni Rupa dan Desain ITB, 2026)
Despite its favorable outlook, Islamic religious tourism in Indonesia faces persistent challenges, particularly the low adoption of technology stemming from a socio-cultural strategy mismatch. This study aimed to identify user personas, appropriate platform features, and effective market penetration strategies for a Nusantara Islamic religious tourism platform. Employing a mixed-method design, the study applied Design Thinking principles (empathize, define, ideate, prototype, and test) alongside Graham Robertson's adoption theory. Data were collected from 4 in-depth interview participants, 32 questionnaire respondents, and 10 prototype evaluators drawn from the Ahlusunnah Wal Jama'ah (ASWAJA) Muslim community in Nusantara. The findings confirmed three core platform features: (1) religious tourism destination information, (2) hotel booking, and (3) worship and prayer guidance. Two dominant adopter categories were identified — Trend Influencer and Late Mass — corresponding to Craft Brand and Power Player strategies aligned with Blue Ocean and Red Ocean approaches, respectively. Theoretically, this study contributes a context-adaptive model integrating Design Thinking with Robertson's market penetration framework, while offering practical recommendations for platform developers, policymakers, and destination managers seeking culturally aligned digital innovation.